2017
DOI: 10.1590/s1679-45082017ao3613
|View full text |Cite
|
Sign up to set email alerts
|

Jumping in aquatic environment after sciatic nerve compression: nociceptive evaluation and morphological characteristics of the soleus muscle of Wistar rats

Abstract: Objective To evaluate the effect of jumping in aquatic environment on nociception and in the soleus muscle of trained and not trained Wistar rats, in the treatment of compressive neuropathy of the sciatic nerve.Methods Twenty-five Wistar rats were distributed into five groups: Control, Lesion, Trained + Lesion, Lesion + Exercise, and Trained + Lesion + Exercise. The training was jumping exercise in water environment for 20 days prior to injury, and treatment after the injury. Nociception was evaluated in two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Peripheral nervous injuries directly affect the muscle tissue because they interrupt the neuromuscular communication ( 18 ) and result in loss of function of innervated organ, ( 19 ) and reduction of cross-sectional section and muscle diameter of muscle fibers. ( 20 ) In our study, changes in muscle structure, such as weight reduction, diameter and muscle area were observed in injured groups since 8 th day after surgery, but, when cryotherapy was done, these changes were observed only in 15 th day after surgery, therefore, physiotherapeutic modality reduced speed of muscle atrophy.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Peripheral nervous injuries directly affect the muscle tissue because they interrupt the neuromuscular communication ( 18 ) and result in loss of function of innervated organ, ( 19 ) and reduction of cross-sectional section and muscle diameter of muscle fibers. ( 20 ) In our study, changes in muscle structure, such as weight reduction, diameter and muscle area were observed in injured groups since 8 th day after surgery, but, when cryotherapy was done, these changes were observed only in 15 th day after surgery, therefore, physiotherapeutic modality reduced speed of muscle atrophy.…”
Section: Discussionmentioning
confidence: 47%
“…( 24 ) After nervous injury, in addition to described morphological changes, we also observed changes in muscle excitability ( 25 ) and increase in density of conjunctive tissue, ( 24 ) although in experimental models this fact not always occur. ( 20 )…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggested that dizocine combined with ropivacaine has a significant analgesic effect in rat model of peripheral nerve compression. Peripheral nerve damage directly affects muscle tissue because they disrupt neuromuscular communication and results in loss of function of the innervating organs and cause muscle fiber cross-section and muscle diameter decrease [15][16][17]. Chronic sciatic nerve compression is characterized by variable degree of degeneration in great myelinated axons and endoneural edema [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…1 Tratamentos não cirúrgicos, como o exercício físico, podem atuar na regeneração nervosa periférica. 4 O exercício físico executado no ambiente aquático induz efeitos fisiológicos que proporcionam benefícios aos sistemas cardiovascular, esquelético, muscular e nervoso que aumentam o processo de reparação tecidual. 6 A natação auxilia na regeneração do nervo ciático em coelhos, 7 peixes 8 e ratos.…”
Section: Introductionunclassified